Identities for the total number of parts in partitions of integers - Knopfmacher, Arnold; Robbins, Neville (Utilitas Mathematica, 2005)
We consider the totel number of parts in partitions of the natural number n, and derive identities relating this function to the number of partitions and to other familiar number theoretic functions. The total number of parts in partitions with distinct parts and partitions with other restrictions is also considered.